Desafios, questionamentos e práticas de leitura e escrita no Ensino Fundamental II: sequência didática sobre o gênero currículo - Ribeiro, Jessika Gama (2015)
The general objective of this research is to identify and understand the ways of causing changes in the teaching-learning process of reading and writing curriculum gender in a class of 9th Year of Secondary School (EF II) and as a specific objective to analyze how the interaction happens through a didactic sequence (SD) on the guided curriculum gender in the contents of Portuguese Language provided by São Paulo Municipal Education. Thus, the question that guides this research is how the teacher-researcher (PP) and students interact in the classroom to develop the process of reading and writing curriculum genre through a SD? To achieve the proposed objectives and answer these questions, this research is based on Socio-Historical-Cultural Theory (TSHC), the relevant concept is the language design for the construction of knowledge through social interactions (Vygotsky, 1934 / 2007; 1934/2008); the concept of critical collaboration proposed by Magalhães (2011). It is also presented, the teaching-learning proposal of the National Curricular Parameters for Portuguese Language (PCN-LP) and also brings the Genevan notion of didactic sequence (SD) for didactization of genres (DOLZ And SCHENEUWLY, 2004). In terms of methodology, this research agenda on the Critical Research Collaboration (PCCol), based on Magellan (2011); Oliveira and Magalhaes (2011) and Ninin (2011; 2013), aimed at intervention in the school context, understanding and transformation of praxis through the reflective process permeated by contradiction. For the production data were recorded 15 Portuguese classes taught by the teacher-researcher (PP), in a class of 9th grade. For analysis and discussion of the data, the reference is in the interaction based on Kerbrat-Orecchioni (2006); in Ninin (2013) and the types of questions; and Gryner (2000) and the result of argument. The survey results indicate that the SD was essential to provide meaningful activities and that can apply to students; Furthermore, the questions, even if carried out only by PP, propitiated argumentative sequences between students that were gradually being transformed